Impact of Carbohydrate Counting Errors on Glycemic Control in Type 1 Diabetes. Issue 27 (2018) - Reiterer, Florian; Freckmann, Guido; Re, Luigi del
Abstract: Patients with type 1 diabetes mellitus (T1DM) typically determine their bolus insulin needs based on methods from Advanced Carbohydrate Counting (ACC). In ACC the amount of required bolus insulin is assumed to be directly proportional to the carbohydrate content of the ingested meal. It is well known that many T1DM patients have difficulties to accurately estimate meal carbohydrates. Though these estimates are used for calculating the meal bolus amount, there is a scarcity of data on how estimation errors affect glycemic control. The current paper analyzes the effect of carb counting errors on glycemic outcomes during basal-bolus-therapy in a simulation study using so-called Deviation Analyses. Furthermore, the effect of inaccurate estimates on the settings of the insulin therapy is studied by means of the previously published Adaptive Bolus Calculator (ABC) algorithm. It is found that whereas random carb counting inaccuracies indeed do lead to an inferior glycemic control, systematic biases in the estimates are expected to hardly affect the results since these are usually implicitly accounted for in the therapy settings.